Adsorption Of Cr(VI) Ions Using Sugar Palm Fruit Peel (Arenga Pinnata) Immobilized in Ca-Alginate Bead - Lestari, Intan; Prasetyo, Widy; Lasmana Tarigan, Indra; Permana, Edwin (Jurnal Rekayasa Kimia & Lingkungan, 2022)
physiological or metabolic processes that can cause cancer in humans. Adsorption is one of the method that is quite effective for removing Cr(VI) in waters because this method uses low cost with good efficiency. Sugar palm fruit peel waste can be used as an adsorbent because it contains active compounds such as carbohydrates, proteins, fats that can play a role in the absorption of metal ions. This sugar palm peel waste will be immobilized using a Ca-alginate medium to increase the absorption of mechanical forces in the adsorption process. The sugar palm fruit peel was activated using 4% NaOH, which was then immobilized by Ca-alginate. The adsorbent was tested to determine its functional group using FTIR and using SEM EDX to see the surface morphology and the elements present in the adsorbent. The results showed that the optimum absorption of metal ions Cr(VI) using Ca-alginate immobilized palm peel as adsorbent at optimum pH 2 with an efficiency of 63% and adsorption capacity of 0.35396 mg/g, the optimum contact time was 75 minutes with an efficiency of 73, 83% and adsorption capacity of 0.41314 mg/g and the optimum concentration at 150 ppm with adsorption capacity of 13.15185 mg/g